Red Herring in Returned Traveler: Drug Reaction With Eosinophilia and Systemic Symptom (DRESS) Syndrome Mimicking Sepsis. Issue 6 (28th August 2014) - Lim, Hui Yin; Huang, Gene Khai Lin; Torresi, Joseph; Johnson, Douglas
Abstract : We report a case of a 51‐year‐old Han Chinese recently returned traveler, who was admitted with a generalized maculopapular rash, fevers, shock, and multi‐organ failure. Extensive investigations failed to reveal an infective cause. Skin biopsy findings together with the recent commencement of allopurinol raised a diagnosis of drug reaction with eosinophilia and systemic symptom syndrome. High‐dose prednisolone was commenced and the patient made a rapid recovery. This case highlights that not all sepsis‐like presentations in returned travelers are due to infective causes and that severe drug reactions need to be considered in the differential diagnosis.